Beneath Copper Falls - Coble, Colleen (Coble, Colleen. Rock Harbor series, 2017)
"As a 911 dispatcher, Dana Newell takes pride in being calm in tough circumstances. In addition to her emotionally-charged career, she's faced enough emergencies in her own life. She recently escaped her abusive fiancé to move to tranquil Rock Harbor where she hopes life will be more peaceful. But the idyllic town hides more danger and secrets than it first appeared. Dana is continually drawn to her new friend Boone, who has scars inside and out. Then she answers a call at her job only to hear a friend's desperate screams on the other end. Soon, the pain in her past collides with the mysteries of her new home - and threatens to keep her from the future she's always wanted." - Provided by publisher.